Ocena stanu środowiska gruntowego w rejonie poprzemysłowym Zakładów Metalurgicznych "Trzebinia" (ZM I) = Assessment of soil environment of "Trzebinia" Metal Company postindustrial area - Kot-Niewiadomska, Alicja (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Soil environment of Trzebinia Metal Company and adjacent areas for many years are exposed to multi-directional degradation connected with diversity industrial sources. Research results cleary indicate that chemical degradation of examined area is connected with extremely high concentration of As, Cd, Cu, Zn and Pb. The concentration of Ag, Fe, Ni, Mn and Tl are also increased.
Keywords: teren poprzemysłowy; Zakłady Metalurgiczne "Trzebinia"; środowisko gruntowe; postindustrial area; "Trzebinia" Metal Company; soil environment